Stable Isotopes, Chronology, and Bayesian Models for the Viking Archaeology of North-East Iceland. (2nd January 2019) - Hamilton, W. Derek; Sayle, Kerry L.
ABSTRACT: This paper reviews the results of a long-term research project that used stable isotope analyses (δ 13 C, δ 15 N, δ 34 S) and Bayesian mixing models to better model the chronology for a presumed Viking Age cemetery at Hofstaðir, near Lake Mývatn in north-east Iceland. δ 13 C and radiocarbon dating indicated that many of the individuals consumed a large amount of marine protein, which results in a marine reservoir effect (MRE), making ages older than expected. In addition to the MRE, geological activity in the region has the potential to introduce massive quantities of radioactive 'dead' carbon into the freshwater system, resulting in a very large freshwater reservoir effect (FRE) that can offset radiocarbon ages on the order of a few thousand years. The radiocarbon dates of organisms that derive an unknown proportion of their carbon from both marine and freshwater reservoirs are extremely difficult to 'correct', or, more appropriately, model. The research not only highlights the complexities of dealing with multiple reservoirs, but also how important it is to develop models that are temporally and geographically relevant to the site under study. Finally, it shows how this data can be used to inform the development of chronological models for refining the dating for archaeological activity.